PENGARUH MEDIA PAPAN FLANEL TERHADAP KEMAMPUAN KOGNITIF ANAK DI RA JAM’IYYATUSH SHOOLIHIIN KELURAHAN TANJUNG MULIA KECAMATAN MEDAN DELI - Siti Khadijah; Masganti Sit; Sapri Sapri (Universitas Islam Negeri Sumatera Utara, 2019)
The purpose of this study was to find out: (1) determine the effect of flannel board media on children's cognitive abilities in RA Jam'iyyatush Shoolihiin, (2) determine the effect of blackboard media on children's cognitive abilities in RA Jam'iyyatush Shoolihiin, (3) find out the differences in media influence flannel board with whiteboard media on children's cognitive abilities at RA Jam'iyyatush Shoolihiin.This type of research is quantitative research with Quasi Experimental Design. The sampling technique uses simple random with lottery techniques. Data collection instruments using experiments. And data analysis techniques using statistical tests, namely normality test, homogeneity test and hypothesis testing using t-test. The results showed that: (1) There was the influence of the flannel board media on the cognitive abilities of children in RA Jam'iyyatush Shoolihiin, this was seen from t count > t table, namely 8,1832 > 1,68830 (2) There was no effect of the whiteboard media on cognitive abilities of children in RA Jam'iyyatush Shoolihiin, seen from t count < t table, ie 1.0563 < 1.68830, (3) There is a difference in the influence of flannel board media with whiteboard media on children's cognitive abilities in RA Jam'iyyatush Shoolihiin, seen From the post-test hypothesis test of the two classes with t count > t table which is 7.68493> 1.68830.